What difference does God make to morality? - Swinburne, R (Rowman and Littlefield Publishers, 2008)
I’m not going to discuss whether or not there is a God (that’s something I’m argued for a lot over the years), but simply whether if there is a God, that makes any difference to morality., I shall argue that the existence and actions of God make no difference to the fact that there are moral truths; but that the existence and actions of God make a great difference1 to the content of morality, to the seriousness of morality, and our knowledge of morality. I assume a standard Western account of the nature of God, as essentially eternal, omnipotent, omniscient, perfectly good, creator and sustainer of the universe and all that it contains (from moment to moment), the kind of God a ffirmed by Christianity, Judaism and Islam as well as some other religions.